Developing Entrepreneurial Competence among University Students through Gamification-based Entrepreneurship Education - Sari, Juwita; Satria, Vinza Hedi; Pradhani, Fastha Aulia (Jurnal Entrepreneur dan Entrepreneurship (JEE), 2025)
This study examines the challenge of developing engaging and practical entrepreneurship education in the digital era. Using a causal research design, it examines the influence of entrepreneurship education on entrepreneurial competence, mediated by entrepreneurial attitude and mindset. In addition to identifying causal relationships between variables, this study examines the multivariate effects that result from integrating gamification into entrepreneurship learning. Data were collected from undergraduate students and analyzed using PLS-SEM to evaluate inter-variable relationships. The findings indicate that entrepreneurship education has a significant impact on students’ attitudes and mindsets, ultimately influencing their entrepreneurial competence. However, no direct effect of education on competence was found, indicating that mentality and mindset completely mediate this relationship. Gamified learning methods significantly improved students’ understanding of entrepreneurship content. This study presents a novel empirical framework that integrates gamification into a mediation model between education and competence, employing both structural and experimental analysis. Unlike prior studies focusing on direct effects or single-method designs, this research highlights the indirect impact of education. It comprehensively evaluates gamification’s pedagogical value in higher education entrepreneurship programs.